The association between oxidative balance score and muscular dystrophies - Tang, Dupeng; Lin, Lanqing; Zheng, Yixin (Frontiers in Nutrition, 2024)
This research utilized data from the NHANES 2011-2018 study to investigate the connection between the Oxidative Balance Score (OBS) and muscular dystrophies. The analysis included 4,172 individuals, of whom 320 (7.7%) were diagnosed with muscular dystrophies. The study found a significant inverse correlation between the OBS and muscular dystrophies, suggesting that individuals with higher oxidative balance had a lower risk of developing muscular dystrophies. This association remained significant after adjustment for various demographic and medical history factors (For continuous OBS: crude model, odds ratio [OR], 0.95, 95% confidence interval [CI:] 0.94, 0.97, p<0.001;